INFLUENCE OF MILITARY INSTRUCTOR‘S PRACTICAL EXPERIENCE FOR THE QUALITY OF TEACHING IN VILNIUS UNIVERSITY OF APPLIED SCIENCES - Černius, Nerijus (PROFESSIONAL STUDIES: Theory And Practice, 2022)
The article presents a military instructor’s experience in teaching soldiers and the transfer of this experience to the students. Applying various teaching methods in practice it makes easier for both teachers and students to adapt to the new challenges in throughout the study process. Also students’ opinion and assessment of the quality of teaching presents an important segment of the evaluation of this process. The author examined students from the Faculty of Health Care of Vilnius University of Applied Sciences learning outcomes, their opinion on the pedagogical benefits of the subject / module being studied as well as conducted a selfassessment of teaching process. The learning outcomes of 311 students were assessed and 41 student provided feedback on this teaching process. The article reveals various methods of teaching. Ways to improve students’ motivation are assessed, as well as social relations and development of students’ skills necessary for the subject / module being studied. The research results revealed that students appreciate the course and procedures of organizing and conducting lectures of a teacher with experience as a military instructor and applying various forms and methods in this teaching process. Keywords: students, teacher, lecture, teaching process, subject / module.